2009
DOI: 10.1002/jsfa.3763
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic fertilisers and irrigation level on physical and chemical quality of industrial tomato fruit (cv. Nautilus)

Abstract: BACKGROUND: The objective of this work was to study the influence of irrigation and organic fertilisation on quality attributes of tomato fruit (cv. Nautilus) grown for the canning industry. The assay was carried out during two consecutive years (2006 and 2007) in agricultural soil. Nine treatments resulting from the combination of three fertilisation types (sheep manure, a mixture of sheep manure and peat and an inorganic fertiliser (control)) with three levels of drip irrigation (3.30, 5.00 and 6.70 mm day −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 37 publications
5
7
0
1
Order By: Relevance
“…However, it should be noted that the NO3 -content in the tomato fruit remained well below the limits of the European guidelines (European Commission, 2011). The mean values of the remaining qualitative parameters (i.e., DM, Wm, Dm, CI, pH, SSC, TA, Ca 2+ , Na + ) were in agreement with the data from other studies (Mahajan and Singh, 2006;Favati et al, 2009;Madrid et al, 2009).…”
Section: Qualitative Traits and Microbial Pollution Of The Tomato Plasupporting
confidence: 90%
See 1 more Smart Citation
“…However, it should be noted that the NO3 -content in the tomato fruit remained well below the limits of the European guidelines (European Commission, 2011). The mean values of the remaining qualitative parameters (i.e., DM, Wm, Dm, CI, pH, SSC, TA, Ca 2+ , Na + ) were in agreement with the data from other studies (Mahajan and Singh, 2006;Favati et al, 2009;Madrid et al, 2009).…”
Section: Qualitative Traits and Microbial Pollution Of The Tomato Plasupporting
confidence: 90%
“…The SSC and TA decreased significantly from the first (HD1) to the last (HD4) harvest dates, with decreases from 6.3 to 5.3 °Brix and from 0.45 to 0.19 g 100 mL -1 , respectively. In general, in the course of the trial, the SSC and TA were consistent with data from other field experiments on tomato (Richardson et al, 2006;Madrid, 2009).…”
Section: Qualitative Traits and Microbial Pollution Of The Tomato Plasupporting
confidence: 87%
“…Trabalhos que revelam efeito negativo do déficit hídrico sob o peso dos frutos foram evidenciados por Madrid et al (2009) Alvarenga (2004) ressalta-se que a ocorrência de temperatura elevada do local na época de floração, aumenta o número de abortamento das flores resultando em queda de produtividade.…”
Section: Resultsunclassified
“…. Madrid et al (2009) assessed the effects of organic fertilization and irrigation rates on tomato crops and reported that the water deficit reduces leaf area and affects photosynthesis and water accumulation by the fruits and consequently, the fruit weight. Other authors also evaluated irrigation management in tomato crops and found responses of FW, with decreasing irrigation frequency, similar to those found in the present work (KOETZ et al, 2010;SILVA et al, 2013).…”
Section: Revmentioning
confidence: 99%